Help for people in country areas (Government Printer, 1991)
This book contains information about a range of Commonwealth and State government assistance available to people in country areas, including farming families. However, it does not include rates of payment and income and asset levels. It provides details of how to contact each department for more information. "The Rural Book", published as part of the Dept. of Primary Industries and Energy Countrylink program, may also contain more information about other Commonwealth assistance.